A novel intraperitoneal therapy for gastric cancer with DFP‐10825, a unique RNAi therapeutic targeting thymidylate synthase, in a peritoneally disseminated xenograft model. (14th October 2019) - Ando, Hidenori; Fukushima, Masakazu; Eshima, Kiyoshi; Hasui, Taichi; Shimizu, Taro; Ishima, Yu; Huang, Cheng‐Long; Wada, Hiromi; Ishida, Tatsuhiro
Abstract: Purpose: In advanced gastric cancer, peritoneal dissemination is a life‐threatening mode of metastasis. Since the treatment options with conventional chemotherapy remain limited, any novel therapeutic strategy that could control such metastasis would improve the outcome of treatment. We recently developed a unique RNA interference therapeutic regimen (DFP‐10825) consisting of short hairpin RNA against thymidylate synthase (TS shRNA) and cationic liposomes. The treatment with DFP‐10825 has shown remarkable antitumor activity in peritoneally disseminated human ovarian cancer–bearing mice via intraperitoneal administration. In this study, we expanded DFP‐10825 to the treatment of peritoneally disseminated gastric cancer. Methods: DFP‐10825 was administered intraperitoneally into mice with intraperitoneally implanted human gastric cancer cells (MKN45 or NCI‐N87). Antitumor activity and host survival benefits were monitored. Intraperitoneal distribution of fluorescence‐labeled DFP‐10825 was monitored in this MKN45 peritoneally disseminated mouse model. Results: Intraperitoneal injection of DFP‐10825 suppressed tumor growth in two peritoneally disseminated cancer models (MKN45 and NCI‐N87) and increased the survival time of the MKN45 model without severe side effects. Throughout the treatment regimen, no significant body weight loss was associated with the administration of DFP‐10825. Interestingly, after intraperitoneal injection, fluorescence‐labeled DFP‐10825 retained for more than 72 hours in the peritoneal cavity and selectively accumulated in disseminated tumors. Conclusions: Intraperitoneal injection of DFP‐10825 demonstrated effective antitumor activity without systemic severe adverse effects via the selective delivery of RNAi molecules into disseminated tumors in the peritoneal cavity. Our current study indicates that DFP‐10825 could become an alternative option to improve the outcomes of patients with peritoneally disseminated gastric cancer. Abstract : Intraperitoneal DFP‐10825 showed effective antitumor activity in peritoneally disseminated human gastric cancer–bearing mice. As an alternative treatment regimen, DFP‐10825 has the potential to improve the outcomes of patients with peritoneally disseminated gastric cancer.